Efficacy of fosaprepitant for the prevention of postoperative nausea and vomiting in patients undergoing gynecologic surgery: a multicenter, randomized, double-blind study - Yingjun Zhang; Xiaolin Luo; Qisen Fan; Sha Zhou; Yinqian Kang; Zhongqiao Mo; Jierong Luo; Bin Zheng; Lan Lan; Jingdun Xie (Anesthesiology and Perioperative Science)
Abstract Purpose This study aims to investigate whether adding fosaprepitant to palonosetron and dexamethasone is effective in preventing postoperative nausea and vomiting (PONV) in high-risk patients undergoing gynecologic surgery. Methods Eligible patients undergoing gynecological surgery were randomized into two groups (1:1). One group received fosaprepitant (150 mg) and the other (control) received a placebo infusion. Both groups received a single dose of palonosetron (0.25 mg) and dexamethasone (5 mg) together with therapeutic medication. The primary endpoint was the absence of vomiting and no use of rescue antiemetics during the first 24 h after surgery; complete response rate (CRR). Results CRR was significantly higher in the fosaprepitant group compared to the control group 0–24 h after surgery (P = 0.037; relative risk [RR], 1.116; 95% confidence interval [CI], 1.007 to 1.235). Moreover, CRR was also significantly higher during the 24–48 h (P = 0.004; RR, 1.148; 95% CI, 1.045 to 1.261) and 48–72 h (P = 0.039; RR, 1.083; 95% CI, 1.005 to 1.168) observation periods respectively. The complete control rate was higher in the fosaprepitant group than in the control group during the 0–24 h observation period (P = 0.012; RR, 1.367; 95% CI, 1.067 to 1.751). Nausea and rescue antiemetic use were comparable between the two groups. The severity of vomiting was significantly higher in the fosaprepitant group than in the control group on the second day (P = 0.016). Dynamic pain visual analog scale score was lower in the fosaprepitant group and quality of recovery-15 scores were significantly higher in the same group during 0–24 h observation period (P = 0.018 and 0.005, respectively). Conclusions The triple combination of fosaprepitant, palonosetron, and dexamethasone was superior in the prevention of PONV after gynecologic surgery in high-risk patients. We suggest that for high-risk patients, a triple combination therapy may be a better choice. Trial registration Registered at the Chinese Clinical Trial Registry ( https://www.chictr.org.cn/showproj.html?proj=171741 ) with No. ChiCTR2200060890 on June 13, 2022. Principal investigator: Jingdun Xie.